PRIORITY AREAS OF INNOVATION ACTIVITY IN THE DEVELOPMENT OF FREE ECONOMIC ZONES IN THE WORLD ECONOMY - Qizi , Achilova Shirin Shavkat (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Free Economic Zones (FEZs) have emerged as pivotal platforms for driving innovation, economic growth, and global competitiveness. This article explores the priority areas of innovation within FEZs, emphasizing the key sectors where innovation is most pronounced. Through an analysis of technology and digital transformation, sustainable and green technologies, life sciences, advanced manufacturing, logistics, and education, this study identifies the critical areas where FEZs contribute to the global economy. The findings suggest that these zones are increasingly focusing on high-tech industries, sustainable development, and skill enhancement, making them central to the future of economic policy and business strategy. The article concludes with recommendations for policymakers and businesses on how to leverage FEZs for sustained innovation and economic growth.